Plasmonic meta-electrodes allow intracellular recordings at network level on high-density CMOS-multi-electrode arrays. Issue 10 (October 2018) - Dipalo, Michele; Melle, Giovanni; Lovato, Laura; Jacassi, Andrea; Santoro, Francesca; Caprettini, Valeria; Schirato, Andrea; Alabastri, Alessandro; Garoli, Denis; Bruno, Giulia; Tantussi, Francesco; De Angelis, Francesco
Abstract The ability to monitor electrogenic cells accurately plays a pivotal role in neuroscience, cardiology and cell biology. Despite pioneering research and long-lasting efforts, the existing methods for intracellular recording of action potentials on the large network scale suffer limitations that prevent their widespread use. Here, we introduce the concept of a meta-electrode, a planar porous electrode that mimics the optical and biological behaviour of three-dimensional plasmonic antennas but also preserves the ability to work as an electrode. Its synergistic combination with plasmonic optoacoustic poration allows commercial complementary metal–oxide semiconductor multi-electrode arrays to record intracellular action potentials in large cellular networks. We apply this approach to measure signals from human-induced pluripotent stem cell-derived cardiac cells, rodent primary cardiomyocytes and immortalized cell types and demonstrate the possibility of non-invasively testing a variety of relevant drugs. Due to its robustness and easiness of use, we expect the method will be rapidly adopted by the scientific community and by pharmaceutical companies. A combination of planar porous electrodes, optoacoustic poration and laser scanning allows large-scale recording of intracellular action potentials of cardiomyocyte cultures on CMOS-MEAs.